Ultrasonic isolation of the outer membrane of Escherichia coli with autodisplayed Z-domains - Bong, Ji-Hong; Yoo, Gu; Park, Min; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER SCIENCE INC, 2014)
The outer membrane of Escherichia coli was previously isolated as a liposome-like outer membrane particle using an enzymatic treatment for lysozymes; for immunoassays, the particles were subsequently layered on solid supports via hydrophobic interactions. This work presents an enzyme-free isolation method for the E. coli outer membrane with autodisplayed Z-domains using ultrasonication. First, the properties of the outer membrane particle, such as the particle size, zeta potential, and total protein, were compared with the properties of particles obtained using the previous preparation methods. Compared with the conventional isolation method using an enzyme treatment, the ultrasonic method exhibited a higher efficiency at isolating the outer membrane and less contamination by cytosolic proteins. The isolated outer membrane particles were layered on a gold surface, and the roughness and thickness of the layered outer membrane layers were subsequently analyzed using AFM analysis. Finally, the antibody-binding activity of two outer membrane layers with autodisplayed Z-domains created from particles that were isolated using the enzymatic and ultrasonic isolation methods was measured using fluorescein-labeled antibody as a model analyte, and the activity of the outer membrane layer that was isolated from the ultrasonic method was estimated to be more than 20% higher than that from the conventional enzymatic method. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: FACS-BASED-IMMUNOASSAY; E. COLI; SURFACE DISPLAY; PROTEIN-A; IMMOBILIZATION; BIOSENSOR; CELLS; BETA